National and regional prevalence rates of hypertension in Saudi Arabia: A descriptive analysis using the national survey data - Alenazi, Aqeel M.; Alqahtani, Bader A. (Frontiers in Public Health, 2023)
Background: Limited studies have examined the prevalence of hypertension (HTN) at the national and regional levels in Saudi Arabia. Therefore, this study aimed to examine the national and regional prevalence of HTN in the Saudi population. Methods: This study used the data from household health survey carried out by the General Authority for Statistics in 2017. It included 24,012 households representing the Saudi population across all 13 administrative regions. The diagnosis of HTN was confirmed by a self-reported history of a physician diagnosed HTN. Results: The prevalence of HTN was 9.2% among Saudi population aged 15 years and older. It was relatively higher in women (10%) than in men (8.5%). The prevalence of HTN increased with advancing age (aged 65 years and older), accounting for 55.3% in women and 48% in men; its prevalence was relatively low among the younger age group, accounting for 0.1% in those aged 15–19 years. A large difference was found in the prevalence of HTN between regions, ranging from 6% in Najran region to 10% in Makkah region. Conclusion: This study reported the national and regional prevalence of HTN among Saudi adults using a representative sample with large variations in the prevalence rates according to age, sex, and regions. Older age, men, and Makkah region had higher prevalence of HTN. Our findings will help determine the etiological factors, identify the priorities for healthcare, and generate initiatives for policymakers, and develop preventive and therapeutic strategies for HTN.